Cooperation Creates Special Moral Obligations - Cappelen, Alexander; Gauri, Varun; Tungodden, Bertil (World Bank, Washington, DC, 2018)
A large-scale economic experiment, conducted on a representative sample of the US population, shows that cooperation creates special moral obligations. Participants in the experiment, acting as impartial spectators, transferred significantly more money to an unlucky worker when two individuals had cooperated than when they had worked independently. The authors further show that the effect of cooperation is strongly associated with political affiliation, with Democrats attaching significantly more importance to cooperation as a source of moral obligation than Republicans. The findings shed light on the foundations of redistributive preferences and may contribute to explain the often observed asymmetry in moral concern for different groups of individuals, both nationally and internationally.